Influence of Social Media Use and Product Innovation on Business Development: A Case Study - Yudha Wiranata, Bhisma; Munawaroh, Munawaroh; Dinaloni, Diah (Journal of Business Management and Economic Development, 2024)
The study aims to (1) explain whether or not the use of social media has an influence on the development of the Banjar Bu Machmudah cake business; (2) explain whether product innovation has an influence on the development of the Banjar Bu Machmudah cake business; and (3) explain whether the use of social media and product innovation have an influence on the development of the Banjar Bu Machmudah cake business. This study employs a quantitative method, using multiple linear regression analysis, to explain the impact of social media and product innovation on business development). In this study, the population consisted of all 106 consumers of the Banjar Bu Machmudah cake shop in April 2023. Purposive sampling was utilized, which is a sample technique with specific requirements. Customers who made more than one purchase at the Banjar Bu Machmudah cake shop throughout April were eligible, with 106 people responding. The finding showed that (1) the use of social media has a substantial impact on the business development of Banjar Bu Machmudah cakes., (2) the product Innovation has a big impact on business development in Banjar Bu Machmudah cakes (3) The usage of social media and product innovation has a big impact on business development.